Escape to nature: camping at Banana Campsite, Kampung Kelian Dalam, Baling, Kedah. / Farhan Faat … [et al.] - Faat, Farhan; Ahmad Russlin, Elyssa Maisara; Abdul Rahim Siddiqe, Ashraf Siddik Khan; Azmi, Mohamad Farhan (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
For those in search of a one-of-a-kind camping adventure, Banana Campsite at Kampung Kelian Dalam provides a tranquil retreat Envision a peaceful haven on the banks of a river, where the melody of nature and the sight of lush bamboo trees create an idyllic setting. A picturesque section of the riverbank, the Banana campsite riverside is bordered by lush bamboo trees that sway subtly in the wind. The sound of the river and the earthy river scent fill the air, creating a refreshing and calming tropical atmosphere. If you set up camp here, it will be like having your very own private heaven. Set up your tent and listen to the calming sound of the river while you listen to the sounds of nature at work. Bamboo trees create beautiful shadows as you set up your tent, and the sound of birdsong in the distance adds to the serene atmosphere. The Banana campsite is a stunning natural attraction that you should investigate once you have set up your tent as it winds its way through the countryside, the river creates a dazzling ribbon.